STRATEGI HUMAS DESA CIOMAS RAHAYU DALAM PEMANFAATAN INSTAGRAM SEBAGAI MEDIA KOMUNIKASI DAN INFORMASI PUBLIK - Sakinah, Siti; Santoso, Hudi; Saleh, Amiruddin; Tri Harpin Pranata, Rici; Manisya, Nabila; Zahra Maharani, Khalila (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This study analyzes the communication strategies of the Ciomas Rahayu Village Public Relations in utilizing Instagram as a public communication medium. Using a descriptive qualitative approach, data were collected through interviews and documentation. The findings indicate that Instagram effectively enhances public interaction with the village government. The implemented strategies include consistent posting, two-way communication through comments and messages, and collaboration with local organizations. The application of the 4C theory (Context, Communication, Collaboration, Connection) highlights that active collaboration and connection are key to the successful use of social media.